Understanding participation intention and word-of-mouth intention in voter contact: A framework based on the theory of planned behaviour - Nguyễn Thanh Nhàn (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The participation of citizens in voter contact is one of the crucial issues for the People’s Council at the grassroots level to carry out their duties and legal powers effectively. This study aims to identify the determinants of citizens’ intention to participate and engage in word-of-mouth communication in voter contact activities based on the theory of planned behavior. Survey data from 322 individuals were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The quantitative analysis results indicate that three factors of the theory of planned behavior, including attitude, subjective norm, and perceived behavioral control, positively and significantly influence citizens’ intention to participate. The intention to participate significantly and strongly influences the intention for word-of-mouth communication. Based on the research findings, the authors propose several solutions to enhance citizens’ intention to participate and engage in word-of-mouth communication in voter contact in the paper’s concluding section.